The Impact Of Work Environment On Teacher Performance: A Case Study At Senior High School - Ikhsan, Muhamamd; Irawati, Irawati; Herlinda, Fitra (Jurnal Administrasi Pendidikan dan Konseling Pendidikan, 2024)
This study aims to analyze the influence of the work environment on the performance of educators at Senior High School 1 Bangkinang Kota. A quantitative approach was employed, utilizing a total sampling technique where all 84 educators were included as the sample. Data were collected using questionnaires and analyzed through simple linear regression with the assistance of SPSS software. The results revealed that the work environment at Senior High School 1 Bangkinang Kota was perceived as good, with 58.3% of respondents agreeing with the work environment indicators. The educators' performance was also rated as good, with 51.2% of respondents providing positive feedback. Statistical analysis indicated a significant influence of the work environment on educators' performance, with a t-value of 8.943 exceeding the t-table value of 1.989 and a significance level of 0.000 (below 0.05). The determination coefficient (R²) of 0.446 suggested that 44.6% of educators' performance is influenced by the work environment, while 55.4% is affected by other variables not examined in this study. These findings emphasize the importance of a conducive work environment in supporting the improvement of educators' performance. Therefore, it is recommended that the school, particularly the principal, continue to foster a comfortable and supportive work atmosphere to optimize the performance of educators.